A clinical and microbiological evaluation of systemic and local metronidazole delivery in adult periodontitis patients - KADİR, TANJU (My University, 1997)
The present study describes results on selected clinical and microbiological parameters obtained by treatment with local (Elyzol) and systemic (Flagyl) use of metronidazole alone and/or mechanical subgingival debridement in adult periodontitis. Patients were randomly divided into local and systemic treatment groups each comprising 5 individuals in each of whom 4 sites (one site/ quadrant) with a probing depth of > or = 5 mm were selected and treated with separate treatment modalities. The overall treatment design provided 6 different test groups. Groups of quadrants received: (1) scaling and root planing; (2) local metronidazole treatment; (3) systemic metronidazole treatment; (4) local metronidazole combined with scaling and root planing; (5) systemic metronidazole combined with scaling and root planing; (6) no treatment. The microbiological and clinical effects of treatment modalities were monitored over a period of 42 days. All treatments resulted in clinical improvements (gingivitis, probing pocket depth, attachment level) except for the untreated group. Parallel to the clinical changes, all treatments reduced the number of total bacteria and proportions of obligately anaerobic microorganisms. Although both of the combined treatment groups responded to therapy with better resolution of infection that the pure mechanical and pure metronidazole treatments, local metronidazole in combination with scaling and root planing seems to be more effective in terms of producing both clinical and microbial improvements.
Keywords: Adult; Female; Humans; Middle Aged; Male; Follow-Up Studies; Administration, Topical; Colony Count, Microbial; Anti-Infective Agents, Local; Porphyromonas gingivalis; Administration, Oral; Gels; Periodontal Pocket; Periodontal Attachment Loss; Root Planing; Prevotella intermedia; Aggregatibacter actinomycetemcomitans; Dental Scaling; Fusobacterium; Gingivitis; Glycerides; Metronidazole; Periodontitis; Sesame Oil